LỒNG GHÉP CÁC VẤN ĐỀ MÔI TRƯỜNG TRONG PHÁT TRIỂN KINH TẾ XÃ HỘI: TRƯỜNG HỢP NGHIÊN CỨU Ở HAI TỈNH QUẢNG TRỊ VÀ HÀ GIANG - Trung, Trần Chí (2016)
Environmental mainstreaming is the informed inclusion of relevant environmental concerns and issues into plans, policy process, and actions of different sectors at different levels. In reality, only if people take into consideration and solve environmental issues are people facing environmental consequences. This paper provides the current situation of environmental maintreaming at the two study sites in order to show the urgent needs for environmental mainstreaming into socio-economic development. Beside the challenges in environmental mainstreaming have been discussed by other studies such as short term economic development priority; coordination among relevant agencies, cultural and behavior constraints this paper also highlights the other challenges in mainstreaming environment as political willing, transparency and capacity in identifying strategic environmental issues. In addition, the risk of bottom - up planning needs to be taken into account in integrating environment into socioeconomic development.